2022
DOI: 10.4049/jimmunol.2200044
|View full text |Cite
|
Sign up to set email alerts
|

BCR-Associated Protein 31 Regulates Macrophages Polarization and Wound Healing Function via Early Growth Response 2/C/EBPβ and IL-4Rα/C/EBPβ Pathways

Abstract: The BCR-associated protein 31 (BAP31), a transmembrane protein in the endoplasmic reticulum, participates in the regulation of immune cells, such as microglia and T cells, and has potential functions in macrophages that remain to be unexplored. In this study, we designed and bred macrophage-specific BAP31 knockdown mice to detect the polarization and functions of macrophages. The results revealed that M2 macrophage-associated genes were suppressed in mouse bone marrow–derived macrophages of Lyz2 Cre-BAP31flox/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…C/EBPβ is one of the key transcription factors that are clearly associated with anti-inflammatory macrophage polarization, 32 while cAMP stimulates the activity of PKA, which subsequently phosphorylate CREB to transcribe C/EBPβ expression. 33 Therefore, we investigated whether Pde3b modulate anti-inflammatory macrophage polarization through cAMP-PKA-CREB-C/EBPβ signaling.…”
Section: Resultsmentioning
confidence: 99%
“…C/EBPβ is one of the key transcription factors that are clearly associated with anti-inflammatory macrophage polarization, 32 while cAMP stimulates the activity of PKA, which subsequently phosphorylate CREB to transcribe C/EBPβ expression. 33 Therefore, we investigated whether Pde3b modulate anti-inflammatory macrophage polarization through cAMP-PKA-CREB-C/EBPβ signaling.…”
Section: Resultsmentioning
confidence: 99%
“…Two in vitro MEFs cell culture models demonstrated that BAP31-deficiency repressed the expression of adipogenic markers, and prevented the differentiation to adipocytes. When induced to differentiation, growth arrested preadipocytes synchronously reenter the cell cycle and undergo the required process of MCE, followed by the expression of genes aiming to adipocyte phenotype, including Cyclin D1, Cebpβ, cdk2-cyclin E, and so on 36 , 37 . BAP31-deficiency inhibited Cyclin D1 expression and reduced MCE in 3T3-L1 preadipocytes, consequently attenuated the process of adipogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…66009-1-Ig) was purchased from Proteintech (Chicago, IL, USA). The Ab against BAP31 was raised in our laboratory as previously described [7]. For cell stimulation, anti-mouse IgM and anti-CD40 were purchased from Invitrogen (catalog no.…”
Section: Abs and Reagentsmentioning
confidence: 99%
“…It has been observed that BAP31 is predominantly associated with mature B cells expressing the antigen receptor membrane IgD, while its association with membrane IgM is relatively weak [6]. BAP31 has been found to impact various functions of macrophages, such as angiogenesis and skin fibrosis, during the wound-healing process through IL-4Rα [7]. Given its significance in diverse immune cells, it is necessary to further understand the role of BAP31 in the development of B cells.…”
Section: Introductionmentioning
confidence: 99%